Contemporary outcomes of coronary artery bypass grafting in obese patients. Issue 3 (16th January 2020) - Chan, Patrick G.; Sultan, Ibrahim; Gleason, Thomas G.; Wang, Yisi; Navid, Forozan; Thoma, Floyd; Kilic, Arman
Abstract: Background: This study evaluated the impact of obesity on outcomes of coronary artery bypass grafting (CABG) with particular attention to cases using bilateral internal mammary arteries (BIMAs). Methods: Patients undergoing isolated CABG from 2011 to 2017 at a single institution were categorized by body mass index (BMI): 18.5 to 24.9 kg/m 2, 25.0 to 29.9 kg/m 2, 30.0 to 34.9 kg/m 2, and ≥35 kg/m 2, respectively. The primary outcomes were mortality and readmission. Subgroup analysis was performed on CABGs using BIMAs. Adjusted Cox model curves were used for survival analyses and cumulative incidence function for readmissions. Results: A total of 4980 patients underwent CABG with BMIs of 18.5 to 24.9 kg/m 2 (17.8%; n = 884), 25.0 to 29.9 kg/m 2 (35.0%; n = 1745), 30.0 to 34.9 kg/m 2 (27.5%; n = 1368), and ≥35 kg/m 2 (19.7%; n = 983), respectively. Patients with BMI 18.5 to 24.9 kg/m 2 had a higher overall Society of Thoracic Surgeons predicted risk of mortality. Adjusted survival was similar across BMI groups, and readmission risk was highest in those with a BMI of 18.5 to 24.9 kg/m 2 ( P = .01). Increasing BMI was associated with higher rates of postoperative deep sternal wound infection (DSWI). CABG was performed with BIMA in 820 (16%). In patients undergoing CABG with BIMA use, there were no differences in survival, readmissions, or DSWI rates between BMI groups. Conclusions: CABG, including with the use of BIMA, can be performed in obese patients without an increased risk of mortality or hospital readmission out to 5 years. Although rates of postoperative DSWI increase with increasing BMI, this finding did not appear to be magnified in patients with BIMA, although the sample size was limited in this subanalysis. These data support the notion that BIMA use should not be precluded in the obese.